Modification of the existing maximum residue levels for fluroxypyr in chives, celery leaves, parsley, thyme and basil and edible flowers - Anastassiadou, Maria (EFSA J, 2020)
In accordance with Article 6 of Regulation (EC) No 396/2005, the applicant Landesanstalt für Landwirtschaftund Gartenbau (LLG) submitted two applications to the competent national authority in Germany to modify the existing maximum residue levels (MRLs) for the active substance fluroxypyr in chives, celery leaves, parsley, thyme and basil and edible flowers. The data submitted in support of the request were found to be sufficient to derive MRL proposals for the commodities under consideration, except for thyme for which a tentative MRL proposal was derived for further risk management considerations. Adequate analytical methods for enforcement are available to control the residues of fluroxypyr in the commodities under consideration at the validated limit of quantification (LOQ) of 0.01 mg/kg. Based on the risk assessment results, EFSA concluded that the intake of residues resulting from the use of fluroxypyr according to the reported agricultural practices is unlikely to present a risk to consumer health.